A Study on Robotic Process Automation (RPA) implementation with emphasis on worker satisfaction and cost reduction: An Indian Bank Case Study - Arora, Tina Amarjit (Digital Repository of Theses, 2025)
This study examines the implementation and impact of Robotic Process Automation (RPA) within the service operations of an Indian bank, focusing on four key dimensions: operational cost reduction, employee satisfaction, implementation challenges, and sustainability of benefits. As automation reshapes the financial services landscape, this research provides an evidence-based evaluation of RPA’s role in enhancing service efficiency and workforce dynamics. A mixed-method research design was employed, integrating employee surveys, interviews, focus groups, and secondary data from organisational reports. Quantitative analysis using T-tests, ANOVA, and regression models were used to assess the relationship between RPA adoption and changes in operational and human performance metrics. Qualitative data was thematically analysed to uncover implementation barriers and enablers from a workforce perspective. The findings demonstrate that RPA contributes meaningfully to cost and productivity improvements by streamlining repetitive tasks and reducing manual error rates. Employees reported enhanced satisfaction and reduced work stress, particularly in roles where automation complemented rather than replaced human input. Challenges identified included integration with legacy systems, change resistance, and the need for structured training and communication during deployment phases. Importantly, the study highlights that the benefits of RPA are perceived as sustainable and scalable when supported by appropriate governance and change management strategies. The alignment between technological capability and organisational readiness emerged as a critical success factor. This research adds to the limited body of literature on RPA deployment in Indian banking and offers practical insights for leaders seeking to balance automation with workforce engagement. It underscores the importance of thoughtful implementation to ensure long-term value from digital transformation initiatives.